أحكام الإنتفاع بالمرهون في الفقه الإسلامي والقانون التايلندي : دراسة تطبيقية في جنوب تايلند - فتنافريجاوونج، أنيس (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2014)
This research aims to study the provisions of utilization of mortgage property in Islamic Law and comparing the provisions of utilization of mortgage property in Thai law. Therefore, to study the process of utilization of mortgage property applied in the Muslim community in southern Thailand. To reach these goals, the researcher collects issues relating to the provisions utilization of mortgage property in the books of jurisprudence ancient and contemporary, and collection of materials related to the provisions utilization of mortgage property in Thai law. The research found that issues of mortgage have mentioning and described by former and present scholars in their books, the researcher only restated and reformulated in the style of the facilitator, and there are points of agreement and points of disagreement between the provisions of utilization of mortgage property in Islamic Law and in Thai law. The research pointed that some of the utilization of mortgage property applied in the Muslim community in southern Thailand suitable to Islamic Law, while the others incompatible with Islamic Law. The research shows that there is potential for the application of Islamic mortgage in Thailand. Finally, the researcher submits the recommendations and suggestions related to the mortgage.